Probation/parole supervision in Aotearoa New Zealand - Polaschek, Devon L. L. (The Routledge handbook on global community corrections, 2024)
Aotearoa New Zealand has a single national correctional system - Ara Poutama Aotearoa (the Department of Corrections) - within which a workforce of probation officers provides sentence oversight for people both on probation supervision (community sentences) and post-imprisonment oversight (“parole”). Probation Officers also assess individuals in order to provide advice to the criminal courts on sentencing options, variations in existing sentences, and sentence non-compliance-related prosecutions. Finally, they contribute to pre-release assessments that support the decision-making of the New Zealand Parole Board. Parole Board decisions determine both when some prisoners will be released - those eligible for early release, and those on indeterminate sentences - and the conditions of the post-release supervision for a larger group of prisoners who have reached mandatory release dates. But much of the work of probation officers is in managing sentences. New Zealand has a hierarchy of relevant community sentences, from intensive forms of supervision for people at high risk of serious crime, electronic monitoring, and home detention through to community work. Most sentences, and probation officers’ roles more generally, encompass a monitoring and compliance component and a rehabilitation/desistance support component, guided by the Risk-Need-Responsivity model, and associated tools for assessing changes in risks, needs and protective factors. The majority of people serving community and custodial sentences in New Zealand are non-European; more than half are indigenous New Zealand Māori. The current strategic plan of Ara Poutama Aotearoa - Hōkai Rangi - focuses intensively on initiatives and innovations to reduce the proportion of Māori caught up in the system. Challenges associated with the COVID pandemic have slowed progress, but a number of new programs underway - if their potential is realized - could transform practice over the next few years, by focusing more on holistic wellbeing and building partnerships with indigenous communities.